Seepage characteristics of fractured rock mass with non-equal width filling under cyclic loading - Shuren Wang; Jiyun Zhang; Chunliu Li; Zhichao Li; Yongqiang Yu (Ain Shams Engineering Journal, 2022)
Fractured rock mass with non-equal width filling often appears in the tunel engineering, the non-equal width ratio is the ratio of the filling width at the seepage inlet to the outlet. To study the seepage characteristics of FFRM (filling fracture rock mass) in the surrounding rock of the Gaoligongshan railway tunnel, the samples of FFRM with different non-equal width ratios were prepared indoors. The permeability coefficient formula of the non-equal width ratio FFRM was deduced for the permeability measurement. Then the triaxial seepage apparatus was used to conduct high and low confining pressure test. Results show that the permeability coefficient of FFRM with non-equal width ratios is a function of multi-parameter interaction, such as seepage outflow, inlet width and filling porosity. The permeability and confining pressure at LCP (low confining pressure) and HCP (high confining pressure) is the power and translation exponential function, respectively. While the relationship between the permeability and non-equal width ratio under confining pressure-seepage condition is the quadratic function. After the first cycle, the permeability loss of the samples under HCP is larger than that of the LCP, and the recovery degree is less than that of the LCP. The SSC (stress sensitivity coefficient) decreases with the increase of the confining pressure, the recovery degree is poor after the first cycle unloading. The trend of the subsequent cycle is almost consistent and the recovery degree is good, which is more obvious under the action of the HCP. The conclusions obtained in this study provide a reference for the stability evaluation of the surrounding rock in the underground engineering.